Factors Associated with Physical Aggression in Pregnant Women and Adverse Outcomes for the Newborn - Elaine Fernandes Viellas; Silvana Granado Nogueira da Gama; Márcia Lazaro de Carvalho; Liana Wernersbach Pinto (Elsevier, 2013)
Objective: To assess the socioeconomic, demographic, and reproductive factors associated with physical aggression during pregnancy, and the negative outcomes for the newborn in two groups of women: adolescents and young adults. Method: Cross-sectional study with a sample of 8,961 mothers who were admitted to hospitals of the city of Rio de Janeiro during delivery. To test the hypothesis of homogeneity of proportions, the chi-squared test was used. Odds ratio and confidence intervals were estimated using logistic regression. Results: 5.0% of the adolescents and 2.5% of the young adult women suffered physical violence during pregnancy. In both groups, the variables associated with physical abuse were lower educational level, lower support from the child's father, and more attempts to interrupt the pregnancy. The increase in alcohol consumption was associated with physical abuse only in the group of adolescents; illicit drug use was only associated with physical abuse in young adults. The children of abused mothers had a two-fold increased chance of neonatal death, and a three-fold increased chance of post-neonatal death. Conversely, good quality prenatal care reduced the chance of physical aggression during pregnancy. Conclusions: The results emphasize the increased chance of neonatal and post-neonatal mortality among children of victims of physical abuse during pregnancy, and indicate the importance of prenatal care to identify women at higher risk of suffering aggression, the appropriate time to provide measures of protection and care for mother and baby. Resumo: Objetivo: Verificar os fatores socioeconômicos, demográficos e reprodutivos associados à agressão física na gestação e os desfechos negativos para o recém-nascido em dois grupos de mulheres: adolescentes e adultas jovens. Método: Estudo transversal com uma amostra de 8.961 puérperas que se hospitalizaram em maternidades do município do Rio de Janeiro por ocasião do parto. Para testar hipó- tese de homogeneidade de proporções foi utilizado o teste χ2. A razão de chances e os intervalos de confiança foram estimados através de regressão logística. Resultados: Foi apontado que 5% das adolescentes e 2,5% das adultas jovens sofreram agressão física na gravidez. Em ambos os grupos, as variáveis associadas com o abuso físico foram: menor nível de escolaridade, menor apoio do pai da criança e maior ten- tativa de interrupção da gestação. O aumento no consumo de bebida alcoólica mostrou associação com o abuso físico apenas no grupo de adolescentes, e o uso de drogas ilícitas somente entre as adultas jovens. Os filhos das puérperas agredidas tiveram duas vezes mais chances de óbito neonatal, e três vezes mais de óbito pós-neonatal. Por outro lado, a assistência pré-natal de boa qualidade reduziu a chance de agressão física durante a gestação. Conclusões: Os resultados alertam para o aumento da chance de óbito neonatal e pós- neonatal entre os filhos das vítimas de agressão física durante a gestação e apontam para a importância do pré-natal na identificação de mulheres sob maior risco de epi- sódios violentos, momento oportuno para o desenvolvimento de ações de proteção e cuidado à mãe e ao bebê. Keywords: Violence against pregnant women, Teenage pregnancy, Infant mortality, Prenatal care, Palavras-chave: Violência contra mulher grávida, Gravidez na adolescência, Mortalidade infantil, Assistência pré-natal